2015
DOI: 10.1159/000381188
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotection of Human Endothelial Cells from Oxidant Stress with CDDO Derivatives: Network Analysis of Genes Responsible for Cytoprotection

Abstract: Aim: To identify drugs that may reduce the impact of oxidant stress on cell viability. Methods: Human umbilical vein endothelial cells were treated with 200 nmol/l CDDO-Im (imidazole) and CDDO-Me (methyl) after exposure to menadione and compared to vehicle-treated cells. Cell viability and cytotoxicity were assessed, and gene expression profiling was performed. Results: CDDO-Im was significantly more cytoprotective and less cytotoxic (p < 0.001) than CDDO-Me. Although both provided cytoprotection by induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 59 publications
2
4
0
Order By: Relevance
“…Since CDDO-Me redirection of TAM activation significantly impaired endothelial cell tube formation, this drug may be important therapeutically in eliciting both immune activation and in combatting angiogenesis. In accordance with recent findings [ 60 ], we failed to observe direct effects of CDDO-Me on EC viability. Furthermore, our studies suggest CDDO-Me effects on EC vascularization are likely mediated indirectly though changes in TAM polarization, rather than through direct effects on ECs, as we did not observe changes in EC tube formation in the absence of CDDO-Me TAM conditioned media.…”
Section: Discussionsupporting
confidence: 93%
“…Since CDDO-Me redirection of TAM activation significantly impaired endothelial cell tube formation, this drug may be important therapeutically in eliciting both immune activation and in combatting angiogenesis. In accordance with recent findings [ 60 ], we failed to observe direct effects of CDDO-Me on EC viability. Furthermore, our studies suggest CDDO-Me effects on EC vascularization are likely mediated indirectly though changes in TAM polarization, rather than through direct effects on ECs, as we did not observe changes in EC tube formation in the absence of CDDO-Me TAM conditioned media.…”
Section: Discussionsupporting
confidence: 93%
“…Both CDDO-Im and CDDO-Me have been shown to elicit protective effects largely through the activation of the transcription factor nuclear factor erythroid 2–related factor 2 ( NRF2 ). 1214 Our previous work with CDDO-Im and CDDO-Me supported published work that demonstrated the central role of NRF2 in homeostasis 11,15 and its role in HMOX1 induction; in addition, it identified potentially new genes that provide additional cytoprotection. A recent study evaluated the kinetics of HMOX1 induction by 4 different transcription factors ( HSF-1, AP-1, NRF2 , and NF-κB ) and showed that they differ in their mechanism of action and kinetics of inducing HMOX1 .…”
Section: Introductionsupporting
confidence: 73%
“…710 Comparing these 2 structurally different forms of CDDO, we previously determined that there is a similar degree of cytoprotection between the 2 compounds; however, significant differences in gene expression were seen between the 2 following a 6-hour treatment on human umbilical vein endothelial cells (HUVEC). 11 The derivative CDDO-Im was shown to induce more gene expression changes than CDDO-Me and resulted in significantly higher expression levels of key cytoprotective genes, including heme oxygenase 1 ( HMOX1 ). 11 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations